2002
DOI: 10.1177/0145445502026002008
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Timeout Ribbon Procedure during Community-Based Instruction

Abstract: Involvement in community-based instruction can be adversely affected when students engage in behavior that interferes with participation in instruction. A multiple probe across settings design with an embedded reversal was used to investigate the effectiveness of the nonseclusionary timeout ribbon procedure for two middle-school students with moderate mental retardation in community and school settings. An athletic wristband served as the timeout ribbon, which functioned as the stimulus for the availability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…One procedure that has been clinically implemented and empirically evaluated to reduce stereotypic behaviors and other aberrant behaviors is the time-out ribbon, also known as time-in ribbon (TIR; for example, Alberto, Heflin, & Andrews, 2002). The time-in procedure consists of having the learner wear a visual stimulus (e.g., ribbon on his or her wrist) as long as he or she is not engaging in the aberrant behavior and the teacher providing reinforcement to the learner.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One procedure that has been clinically implemented and empirically evaluated to reduce stereotypic behaviors and other aberrant behaviors is the time-out ribbon, also known as time-in ribbon (TIR; for example, Alberto, Heflin, & Andrews, 2002). The time-in procedure consists of having the learner wear a visual stimulus (e.g., ribbon on his or her wrist) as long as he or she is not engaging in the aberrant behavior and the teacher providing reinforcement to the learner.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…ribbon (TIR; for example, Alberto, Heflin, & Andrews, 2002). The time-in procedure consists of having the learner wear a visual stimulus (e.g., ribbon on his or her wrist) as long as he or she is not engaging in the aberrant behavior and the teacher providing reinforcement to the learner.…”
mentioning
confidence: 99%
“…First, some individuals may spend their entire lives getting ready without ever having opportunities to participate in the setting for which they are preparing. Second, evidence exists that challenging behaviors are often connected to environmental contexts, thus behaviors displayed at school or home may not be as prevalent in natural community settings when individuals are engaged in preferred activities and are taught appropriate behavior for the setting (Carr & Carlson, 1993;Inge & Dymond, 1994;Alberto et al, 2002). Spending more time in the community may improve overall quality of life and actually eliminate or diminish some challenging behaviors.…”
Section: Issues With Special Populationsmentioning
confidence: 99%
“…The strategies employed to teach skills in community settings should not call undue attention to the individual or involve methods that are perceived negatively by others (Browder et al, 1997;Alberto et al, 2002). Wolfe (1994) found that the types of instructional strategies perceived to be least appropriate included the use of food, exclusionary time-out, overcorrection, and repeated practice.…”
Section: Instructional Prompting Strategiesmentioning
confidence: 99%
“…In the existing literature, timeout is often implemented with high levels of treatment integrity or consistency (i.e., on average greater than 90% integrity; Alberto, Heflin, & Andrews, 2002;Fee, Matson, & Manikam, 1990;Mace et al, 1986;Marlow et al, 1997). In other words, timeout is programmed to be implemented on a certain schedule and the implementation of the programmed schedule is fairly accurate.…”
mentioning
confidence: 99%